Thallium-based heavy inorganic scintillators: recent developments and future perspectives. Issue 3 (7th January 2022) - Kim, HongJoo; Khan, Arshad; Daniel, Joseph; Rooh, Gul; Vuong, Phan Quoc
Abstract : The current development status and future perspectives of Tl-based inorganic scintillators are highlighted in this study. Abstract : The current development status and future perspectives of Tl-based inorganic scintillators are highlighted in this study. The thallium (Tl) ion is known to exhibit highly efficient luminescence in the widely used NaI:Tl +, CsI:Tl +, and recently discovered Cs2 Cu3 I5 :Tl + scintillators. Besides being an efficient luminescence center, Tl possesses high density and atomic number, so that its presence in the host material increases the density and effective atomic number of the scintillators, which provides higher efficiencies for high-energy X- and γ-ray detection. Based on this idea, several novel efficient scintillators were reported by different research groups, which can be utilized in medical imaging, homeland security, space research, nuclear and high energy physics, rare event searches, and oil well logging. An overview of reported Tl-based scintillators and future directions for their improvements are discussed herein based on prior publications.